Implementing a Sharia Green Economy to Address Negative Externalities of Modern Shrimp Pond Waste in Kepanjen Village, Jember Regency - Ika Septin Ananta; Putri Catur Ayu Lestari (Ilmu Ekonomi Manajemen dan Akuntansi, 2026)
This study aims to examine the negative externalities of modern shrimp pond waste in Kepanjen Village, Jember Regency, and to assess the application of the sharia green economy concept as a control measure. The background of the study is based on the inconsistency between the principles of sharia economic development that focus on environmental curiosity and cultivation practices that still cause ecological and social impacts. The study used a qualitative approach with a phenomenological research type. Data were obtained through observation, in-depth interviews with stakeholders, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions with triangulation validity tests. The results show that modern shrimp pond activities give rise to various negative externalities, such as air pollution, increased soil salinity, decreased agricultural productivity, decreased catches for fishermen, and disruption of the organizational environment. The implementation of the sharia green economy has not been optimal because the principles of ecological responsibility, welfare, social justice, and resource efficiency have not been implemented comprehensively. Therefore, regulatory strengthening, increased awareness of business actors, and multi-stakeholder synergy are needed to encourage more effective and sustainable implementation. Based on this description, it can be seen that there is a mismatch between the ideal concept of a sharia green economy and the practice of shrimp pond management in the field, particularly in Kepanjen Village, Jember Regency. Therefore, this study aims to analyze the negative externalities caused by modern shrimp pond waste and examine the application of a sharia green economy to address these issues.